Teacher Survey Smart Application for Thailand Education Version 1.0 - Somsila, Chayakorn; Supakworakul, Chaiwat; Choprapun, Amornrat; Srimuang, Tanawanaphorn (Journal of Education Rajabhat Maha Sarakham University, 2024)
The objectives of this research were to: 1) create and develop a Teacher Survey Smart Application for Thailand Education Version 1.0 and 2) study the satisfaction of using the Teacher Survey Smart Application for Thailand Education Version 1.0. Sample group was education personnel such as teachers, school administrators, etc., in the area of Maha Sarakham Province. The 368 persons of the sample were obtained by multi-stage random sampling and the other 80 persons were obtained by purposive sampling. Research tools were: 1) Opinion Survey Questionnaire on the development of Teacher Survey Smart Application for Thailand Education Version 1.0, 2) User Satisfaction Questionnaire on the Teacher Survey Smart Application for Thailand Education Version 1.0, 3) Expert Quality Evaluation Form of the Teacher Survey Smart Application for Thailand Education Version 1.0 and 4) The Teacher Survey Smart Application for Thailand Education Version 1.0. The data analysis statistics were determined by mean and standard deviation. The research results were as follows: 1) the Teacher Survey Smart Application for Thailand Education Version 1.0 was created and developed using the SDLC process for software development. The application provides the users with convenience, flexibility and reduces the time spent on questionnaire preparation and questionnaire collection. The collected data can be used for statistical analysis which reduce use of paper and time saving, 2) the users’ overall satisfaction of the application was at a high level (x̅=4.39).